Implementasi Ikrar Talak oleh Suami Terhadap Istri Berdasarkan Undang-Undang Nomor 1 Tahun 1974 (Studi Pada Pengadilan Agama Gunung Sugih) - Meita Djohan Oelangan (KEADILAN PROGRESIF, 2016)
Pledge divorce prevailing in Indonesia to be done in the courtroom religion, as stated in Article 39, paragraphs 1 and 2 of Law No. 1 of 1974 on Marriage, Article 65 of Law No. 7 of 1989 on the Religious and Article 115 Compilation Islamic law (KHI). The underlying question in this research is: How to implement a pledge of divorce in the Religious Mount Sugih? The research concludes that the implementation of the pledge of divorce in the Religious Mount Sugih through the stages from case registration by mail for divorce divorce, the appointment of judges, the establishment day of the trial, calling the parties, the proceedings until a decision is legally binding, the proceedings until a decision is legally binding , grace period / appeal, ruling inkrar and execution of the verdict by setting the hearing pledges, calling the parties, the trial implementation of pledges divorce and divorce certificate issuance process; Suggestions To the Religious Courts throughout Indonesia suggested that the implementation of the pledge divorce trial is open although the legislation is so, but in practice there is still covered in a sense has been accessible to the public